M1 Macrophage exosomes MiR‐21a‐5p aggravates inflammatory bowel disease through decreasing E‐cadherin and subsequent ILC2 activation. Issue 6 (10th February 2021) - Lu, Jiaxi; Liu, Deliang; Tan, Yuyong; Deng, Feihong; Li, Rong
Abstract: Abnormal immune regulation is a key feature of the complex pathogenic mechanism of ulcerative colitis (UC). In particular, macrophages and group 2 innate lymphoid cells (ILC2s) are important components of natural immunity that have been shown to play important roles in the pathogenesis of UC, as well as decreased E‐cadherin expression on the colonic mucosa. However, it remains unclear how these components interact with each other. In this study, we investigated the molecular mechanisms of UC mediated by macrophage‐derived exosomes. We showed for the first time that miR‐21a‐5p expression is increased in the peritoneal exosomes of mice with dextran sulphate sodium induced enteritis and that miR‐21a‐5p expression correlates negatively with E‐cadherin expression in enterocytes. Moreover, we confirmed that miR‐21a‐5p was mainly derived from M1 macrophages and demonstrated that KLRG1, a surface inhibitory receptor on ILC2s, participated in excessive ILC2 activation in UC by promoting GATA‐3. In conclusion, our results suggest molecular targets and provide a theoretical basis for elucidating the pathogenesis of UC and improving its treatment.